2018
DOI: 10.1080/21678421.2018.1530264
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cognitive and behavioral change in amyotrophic lateral sclerosis/motor neuron disease: a systematic review of validated screening methods

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…In this way, the instruments could be accurately compared in terms of validity and applicability. Regarding the cognitive screening instruments, the FAB, ALS-CBS, and ECAS show a promising validity (9). Furthermore, no practice effects of the ECAS were found for ALS patients after 6 months and up to 18 months (88).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this way, the instruments could be accurately compared in terms of validity and applicability. Regarding the cognitive screening instruments, the FAB, ALS-CBS, and ECAS show a promising validity (9). Furthermore, no practice effects of the ECAS were found for ALS patients after 6 months and up to 18 months (88).…”
Section: Discussionmentioning
confidence: 93%
“…However, caution should be taken as the MiND-B may miss specific behavioral impairments that are part of the Rascovsky criteria (9). In contrast, the ALS-FTD-Q, BBI and ALS-CBS assess a broad spectrum of behavioral changes, and might, therefore, be more suitable for screening for behavioral changes in ALS-(FTD) patients (9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed neuropsychological characteristics of ALS patients and HC participants by means of the ECAS [117]. The ECAS allows for the assessment of both ALS-specific and ALS-nonspecific neuropsychological characteristics with strong clinical validity [130]. However, we did not find evidence for any differences between ALS patients and HC participants with regard to the ECAS (see Table A1).…”
Section: Study Limitations and Directions For Future Researchmentioning
confidence: 89%
“…Feasibility studies, however, showed that the ECAS might be more suitable, and hence preferable, for screening cognitive function in ALS patients compared to the FAB and MoCA, a finding that is in line with that of another systematic review. 71 While several screening tests have been developed to detect cognitive changes, the Mental Deterioration Battery + Notes: +++ or -= Strong evidence with consistent positive or negative results from multiple studies with good methodological quality or one study with excellent methodological quality. ++ or -= Moderate evidence with consistent positive or negative results from multiple studies with fair methodological quality or one study with good quality.…”
Section: Discussionmentioning
confidence: 99%